2007
DOI: 10.2527/jas.2006-766
|View full text |Cite
|
Sign up to set email alerts
|

Number of fetuses and conceptus growth throughout gestation in lines of pigs selected for ovulation rate or uterine capacity1

Abstract: Selection for 11 generations in swine for ovulation rate (OR) or uterine capacity (UC) resulted in 19.6% greater prenatal survival at term in UC compared with OR. Our objective was to characterize the number of fetuses throughout gestation in each line, including an unselected control (CO) line. Five hundred ninety-three gilts produced over 4 farrowing seasons were subjected to unilateral-hysterectomy-ovariectomy at 160 d of age and mated within line at 280 d of age. Gilts were assigned within sire family to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
66
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 29 publications
11
66
0
Order By: Relevance
“…Post-implantation mortality related with a high OR seems due to effects of intra-uterine crowding and associated competition for space and/or nutrients, both early postimplantation (Geisert and Schmitt, 2002) and throughout the remainder of pregnancy (Foxcroft et al, 2007). Several authors have found a relationship between placental weight and foetal weight at the end of gestation, indicating that foetal development is dependent on placental size (Van Rens, 1989;Freking et al, 2007) and Père et al (1997) found that a high number of embryos at day 35 of pregnancy not only resulted in a higher foetal loss, but also resulted in a lower placental weight and foetal weight of the surviving embryos at 112 days of pregnancy. Thus, in a crowded uterus, placental growth is compromised, which subsequently limits foetal development.…”
Section: Introductionmentioning
confidence: 99%
“…Post-implantation mortality related with a high OR seems due to effects of intra-uterine crowding and associated competition for space and/or nutrients, both early postimplantation (Geisert and Schmitt, 2002) and throughout the remainder of pregnancy (Foxcroft et al, 2007). Several authors have found a relationship between placental weight and foetal weight at the end of gestation, indicating that foetal development is dependent on placental size (Van Rens, 1989;Freking et al, 2007) and Père et al (1997) found that a high number of embryos at day 35 of pregnancy not only resulted in a higher foetal loss, but also resulted in a lower placental weight and foetal weight of the surviving embryos at 112 days of pregnancy. Thus, in a crowded uterus, placental growth is compromised, which subsequently limits foetal development.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of correlated response in litter size has been associated with an increase in the postimplantation mortality [see Bradford (1969) for mice and Freking et al (2007) for pigs]. Response to selection for ovulation rate in rabbits was assessed in previous studies using predicted genetic trends (Laborda et al, 2011(Laborda et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that dietary Arg supplementation from early gestation until day 114 of gestation enhanced sow placental growth, litter size, and weight (Mateo et al, 2007;Gao et al, 2012). However, the sow placental growth has reached maximum in late gestation (McPherson et al, 2004;Freking et al, 2007), instead the efficient placenta in late gestation is physiologically required for rapid fetal growth in the last 20 days of gestation (Biensen et al, 1999;Macpherson et al, 2004). Therefore, it is likely the growth-enhancing effect of Arg on placenta may switch to improve placental efficiency such as stimulating blood flow and nutrients supply.…”
mentioning
confidence: 99%